Upregulated expression of long non-coding RNA MEG3 serves as a prognostic biomarker in severe pneumonia children and its regulatory mechanism. Issue 1 (1st January 2021) - Guo, Jie; Zhang, Ning; Liu, Guozhi; Zhang, Aimei; Liu, Xin; Zheng, Jie
ABSTRACT: Severe pneumonia is a high-mortality disorder in children. The expression and underlying effects of lncRNA maternally expressed 3 (MEG3) were detected. The relationships between MEG3 and other parameters were reported by Pearson correlation. The prognostic importance of MEG3 was assessed by Kaplan-Meier (K-M) curve and COX analysis and its diagnostic potential was uncovered by the receiver operating characteristic (ROC) curve. Luciferase activity assay was performed to demonstrate the target gene of MEG3. Elevated expression of MEG3 and reduced microRNA-29 c (miR-29 c) were evaluated in severe pneumonia children, and a negative relationship between MEG3 and miR-29 c was propounded. MEG3 might function as an independent prognostic indicator. The diagnostic efficiency of MEG3 was also indicated for severe pneumonia children. In MRC-5 cell models and MH-S cell models, lipopolysaccharide (LPS) contributed to the increased expression of MEG3. Interference of MEG3 restricted the upregulation of MEG3 triggered by LPS. Silenced MEG3 protected MRC-5 and MH-S cells against damages managed by LPS on cell apoptosis, viability, and inflammation. MiR-29 c was a ceRNA of MEG3 and the absence of MEG3 abrogated the decreased expression of miR-29 c caused by LPS. Overall, the increased expression of MEG3 and the reduced levels of miR-29 c were identified in severe pneumonia. Prognostic and diagnostic significances of MEG3 provided a novel perspective for severe pneumonia. Disruption of MEG3 alleviated cell injury and inflammation as characterized by high LPS by binding miR-29 c.